1999
DOI: 10.1037/0022-3514.77.5.905
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes and terror management: Evidence that mortality salience enhances stereotypic thinking and preferences.

Abstract: If stereotypes function to protect people against death-related concerns, then mortality salience should increase stereotypic thinking and preferences for stereotype-confirming individuals. Study 1 demonstrated that mortality salience increased stereotyping of Germans. In Study 2, it increased participants' tendency to generate more explanations for stereotype-inconsistent than stereotype-consistent gender role behavior. In Study 3, mortality salience increased participants' liking for a stereotype-consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
209
4
14

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(235 citation statements)
references
References 94 publications
8
209
4
14
Order By: Relevance
“…Previous research has also shown that implicit racism can be reduced by having individuals imagine a counter-stereotypical person (Blair, Ma, & Lenton, 2001). Unfortunately after reminders of mortality individuals prefer a stereotype confirming image of an outgroup member (Schimel et al, 1999). So for future research to be effective in real world settings, such as the life or death situations experienced by police officers and soldiers, not only will it be necessary to lessen stereotypical responses, the future research must also include effective ways of dealing with thoughts of mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has also shown that implicit racism can be reduced by having individuals imagine a counter-stereotypical person (Blair, Ma, & Lenton, 2001). Unfortunately after reminders of mortality individuals prefer a stereotype confirming image of an outgroup member (Schimel et al, 1999). So for future research to be effective in real world settings, such as the life or death situations experienced by police officers and soldiers, not only will it be necessary to lessen stereotypical responses, the future research must also include effective ways of dealing with thoughts of mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, situational manipulations of existential threat, such as making terrorism salient, cause participants to identify themselves as more politically conservative and to score higher on various indicators of system justification (Schimel, Simon, Greenberg, et al, 1999;Thórisdóttir & Jost, 2011;Ullrich & Cohrs, 2007).…”
Section: System Justification Theorymentioning
confidence: 99%
“…At the individual level, stereotypes may help individuals cope with the fear of death. Indeed, according to terror management theory, people hold «cutlural worldviews», i.e., a set of beliefs about the organization of the world and about important values shared within a culture (Schimel et al, 1999). According to this theory, the primary function of these worldviews, of which cultural stereotypes are part, is to protect people against the fear of their own mortality.…”
Section: Functions Of Stereotypesmentioning
confidence: 99%